PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL BERBASIS APLIKASI ETIKA (EDUKASI TENTANG PERSATUAN KITA) BERBANTUAN iSpring UNTUK MENINGKATKAN LITERASI KEWARGANEGARAAN SISWA KELAS V DI SDN 2 TONATAN - Zakiyaturrohmah; Risti Aulia ulfah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop digital learning media based on the ETIKA (Education About Our Unity) application assisted by iSpring to improve civic literacy of fifth-grade students at SDN 2 Tonatan. This research uses a Research and Development (R&D) method with the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of this study were 24 fifth-grade students. Data collection techniques included expert validation questionnaires, student response questionnaires, and pre-test and post-test. The results showed that the ETIKA application has a very high level of validity with material expert scores of 83.3%, media experts 88.7%, and language experts 86%. The practicality level is categorized as very good with an average percentage of 98,83%. The effectiveness test showed an N-gain value of 0.76 (high category) for civic knowledge, 0.22 (low category) for skills, and 0.40 (moderate category) for attitudes. Thus, the ETIKA application is feasible, practical, and effective in improving students' civic literacy.